Pengaruh Financial Knowledge dan Financial Attitude Terhadap Financial Satisfaction Pelaku UMKM Sektor Pariwisata Madura - Aprilia Putri, Dewi; Boy Singgih Gitayuda, M (Bahtera Inovasi, 2023)
This study aims to review the factors that influence financial satisfaction in terms of financial knowledge and financial attitude. The population and sample in this study were 60 MSME respondents in the tourism area in Pamekasan Regency and Sumenep Regency, using a quantitative descriptive approach. Data analysis methods used data testing, multiple linear regression analysis, coefficient of determination test, while hypothesis testing used statistical t (partial) and f (simultaneous) statistical tests assisted by statistical tools, namely IBM SPSS version 25 software. The results showed that: 1) Financial Knowledge has a significant positive effect on Financial Satisfaction; 2) Financial Attitude has no effect on Financial Satisfaction; 3) Financial Knowledge and Financial Attitude have a significant effect simultaneously on Financial Satisfaction.